Greco-Roman Lessons for Public Debt Management and Debt Market Development - Campanaro, Alessandra; Vittas, Dimitri (World Bank, Washington, D.C., 2013)
Greece and Italy initiated efforts to improve public debt management and develop their domestic debt markets respectively in the late 1970s and mid-1980s. At that time, both countries suffered from large and rapidly growing public debt, excessive reliance on short-term bills held by commercial banks, a strong preference of households to save in bank deposits, and a weak presence of institutional investors (pension funds, insurance companies, and mutual funds). Continuing large fiscal deficits, high levels of interest rates and inflation, and serious policy credibility problems impeded the use of long-term instruments. The authors provide a detailed analysis of the characteristics of the instruments that were used in these two countries, their pace of issuance, and their impact on the composition of public debt. The authors note that the main Greco-Roman lesson for developing and transition countries concerns the transition from an excessive reliance on short-term Treasury bills, held by captive banks, to a liquid market with long-term instruments held, and actively traded, by long-term institutional investors. The transition required moving gradually to medium-term instruments, experimenting with innovation, and targeting households and foreign investors, while taking steps to establish policy credibility by lowering fiscal deficits and inflation. When reliance on captive sources of finance was substantially reduced and policy credibility was established, both countries focused on developing active money markets and liquid secondary markets with benchmark issues of fixed-rate long-term securities. They ultimately succeeded in developing active professional markets, using modern practices, targeting well-established European institutional investors, and integrating into the highly sophisticated euro markets. However, integration into the euro markets was the culmination of a prolonged effort of modernization and adaptation and was greatly facilitated by their strong political commitment to achieve economic convergence and join the euro zone.